Conversion of 1T-MoSe2 to 2H-MoS2xSe2−2x mesoporous nanospheres for superior sodium storage performance. Issue 4 (9th January 2017) - Zhang, Junjun; Kang, Wenpei; Jiang, Miao; You, Yu; Cao, Yulin; Ng, Tsz-Wai; Yu, Denis Y. W.; Lee, Chun-Sing; Xu, Jun
Abstract : S-Doped 2H-MoSe2 mesoporous nanospheres converted from 1T-MoSe2 exhibit significantly improved sodium storage performance, including charge/discharge capacity, first Coulombic efficiency, cycling stability, and rate capability. Abstract : S-Doped 2H-MoSe2 ( i.e., 2H-MoS2 x Se2−2 x ) mesoporous nanospheres assembled from several-layered nanosheets are synthesized by sulfurizing freshly-prepared 1T-MoSe2 nanospheres, and they serve as a robust host material for sodium storage. The sulfuration treatment is found to be beneficial for removing surface/interface insulating organic contaminants and converting the 1T phase to the 2H phase with improved crystallinity and electrical conductivity. These result in significantly enhanced sodium storage performance, including charge/discharge capacity, first Coulombic efficiency, cycling stability, and rate capability. Coupled with benefits from in situ carbon modification and its mesoporous morphology, the 2H-MoS2 x Se2−2 x ( x = 0.22) nanosphere anode can maintain a reversible capacity of 407 mA h g −1 after 100 cycles with no observable capacity fading at a high current density of 2.0 A g −1 . This value is much higher than those of the anode fabricated with the freshly-prepared 1T-MoSe2 (95 mA h g −1 ) and the annealed 2H-MoSe2 (144 mA h g −1 ) samples. As the current density rises from 0.05 to 5.0 A g −1 (100-fold increase), the discharge capacity retention is significantly increased from 39% before sulfuration to 65% after sulfuration. This superior electrochemical performance of the 2H-MoS2 x Se2−2 x electrode suggests a promising way to design advanced sodium host materials by surface/interface engineering.